Reviewing the Oil Price - GDP Growth Relationship: A Replication Study - Lanouar Charfeddine; Tony Klein; Thomas Walther (Queen's University Belfast, Queen's Management School, 2020)
This paper presents a thorough replication of Hamilton (2003) which in turn replicates and extends the findings of four seminal papers regarding the oil price-GDP growth relationship. Firstly, we replicate the empirical results obtained with the oil price measures of Hamilton (1983), Mork (1989), Lee (1995), Hamilton (1996), and Hamilton 2003) by using an identical data set of real and nominal oil prices. Secondly, we extend the data sets to 2019Q4 and apply the same methodology. We find that for more recent data the explanatory power of the proposed oil price measures on GDP growth rates is still present, albeit on a slightly weaker magnitude. Extending the ARX(4), we only find little evidence that oil price decreases impact GDP growth rates on the full data set. Parameter stability tests suggest that the impact of oil price decreases might be limited to certain periods
Keywords: C24; E32; F43; Q43; C24; E32; F43; Q43; 330